Alterations of Oxidative Stress Indicators, Antioxidant Enzymes, Soluble Sugars, and Amino Acids in Mustard [Brassica juncea (L.) Czern and Coss.] in Response to Varying Sowing Time, and Field Temperature - Chauhan, Jyoti; Srivastava, J. P.; Singhal, Rajesh Kumar; Soufan, Walid; Dadarwal, Basant Kumar; Mishra, Udit Nandan; Anuragi, Hirdayesh; Rahman, Md Atikur; Sakran, Mohamed I.; Brestic, Marian; Zivcak, Marek; Skalicky, Milan; et al. (Frontiers in Plant Science, 2022)
The impact of elevated temperature at the reproductive stage of a crop is one of the critical limitations that influence crop growth and productivity globally. This study was aimed to reveal how sowing time and changing field temperature influence on the regulation of oxidative stress indicators, antioxidant enzymes activity, soluble sugars (SS), and amino acids (AA) in Indian Mustard. The current study was carried out during the rabi 2017–2018 and 2018–2019 where, five varieties of mustard viz. Pusa Mustard 25 (PM-25) (V1), PM-26 (V2), BPR-541-4 (V3), RH-406 (V4), and Urvashi (V5) were grown under the field conditions on October 30 (normal sowing; S1), November 18 (late sowing; S2) and November 30 (very late sowing; S3) situations. The S1 and S3 plants, at mid-flowering stage, showed a significant variation in accumulation of SS (8.5 and 17.3%), free AA (235.4 and 224.6%), and proline content (118.1 and 133%), respectively, and played a crucial role in the osmotic adjustment under stress. The results showed that S3 sowing, exhibited a significant induction of the hydrogen peroxide (H2O2) (110.2 and 86.6%) and malondialdehyde (23.5 and 47.5%) concentrations, respectively, which indicated the sign of oxidative stress in plants. Interestingly, the polyphenol oxidase, peroxidase, superoxide dismutase, and catalase enzyme activities were also significantly increased in S3 plants compared to S1 plants, indicating their significant roles in ameliorating the oxidative stress. Furthermore, the concentration of fatty acid levels such as palmitic, stearic, oleic, and linoleic acids level also significantly increased in S3 plants, which influenced the seed and oil quality. The study suggests that the late sowing significantly impaired the biochemical mechanisms in Indian mustard. Further, the mustard variety V4 (RH-406) was found to be effective for cultivation as well as environmental stress adoption in Indian soils, and it could be highly useful in breeding for developing heat-tolerant genotypes for ensuring the food security.